An Efficient Fault Location Technique on a Compensated Transmission line Using Synchronized Voltage Measurement - Soni, Vinay Kumar; Sharma, Dipesh Kumar (IJRDO - Journal of Electrical And Electronics Engineering, 2015)
The power continuity and quality is affected by the faults occurring in the transmission line between the generator and receiver of the grid supply systems. The detection of fault location is a vital step towards the removal of fault generated in the line. Several fault location techniques are given by the researchers of power sectors. Most techniques of fault location are based on the current measurement at both ends of the line but due to poor accuracy of the current transformers such techniques were required to be replaced by the advanced techniques adopting GPS, optical fibers and PMUs (phasor measurement units). This paper gives an advanced technique for fault location based on synchronous voltage measurement. A compensated transmission line is considered for the analysis and results are given which will prove this technique to be promising for the long length of line. As for the lines having long length the errors approximating 10% due to the poor accuracy of current transformers will lead in a large labor effort in repairing the fault to the fault team, this technique is very much useful for long line lengths as the errors are very small. In this paper circuit is modeled in EMTP-ATP and simulated using MATLAB-SIMULINK and the results are given.